2018
DOI: 10.1155/2018/8432781
|View full text |Cite
|
Sign up to set email alerts
|

Newer Oral Anticoagulants in the Treatment of Acute Portal Vein Thrombosis in Patients with and without Cirrhosis

Abstract: Background Newer oral anticoagulants (NOACs) are being utilized increasingly for the treatment of venous thromboembolism (VTE). NOAC use is the standard of care for stroke prophylaxis in nonvalvular atrial fibrillation and treatment of acute VTE involving extremities and pulmonary embolism. In contrast, most guidelines in the literature support the treatment of acute portal vein thrombosis (PVT) with low molecular weight heparin (LMWH) and vitamin K antagonists (VKA). Literature evaluating NOAC use in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 47 publications
1
71
0
1
Order By: Relevance
“…69,70 The use of direct oral anticoagulants has been evaluated in splanchnic vein thromboses. Although the use of direct oral anticoagulants for Budd-Chiari syndrome and portal vein thrombosis is rapidly increasing, [71][72][73][74] studies remain limited if not anecdotal. Indeed, the small numbers of patients in studies evaluating Budd-Chiari syndrome, recent portal vein thrombosis and portal cavernoma in the absence of cirrhosis, 31,52 and portal vein thrombosis in patients with cirrhosis, 65 prevents drawing any conclusions and making any recommendations.…”
Section: Irec T or Al Anti Coag Ul Ants And S Pl An Chni C Vein Tmentioning
confidence: 99%
“…69,70 The use of direct oral anticoagulants has been evaluated in splanchnic vein thromboses. Although the use of direct oral anticoagulants for Budd-Chiari syndrome and portal vein thrombosis is rapidly increasing, [71][72][73][74] studies remain limited if not anecdotal. Indeed, the small numbers of patients in studies evaluating Budd-Chiari syndrome, recent portal vein thrombosis and portal cavernoma in the absence of cirrhosis, 31,52 and portal vein thrombosis in patients with cirrhosis, 65 prevents drawing any conclusions and making any recommendations.…”
Section: Irec T or Al Anti Coag Ul Ants And S Pl An Chni C Vein Tmentioning
confidence: 99%
“…Direct‐acting oral anticoagulants (DOACs) or non‐VKA oral anticoagulants like dabigatran, rivaroxaban, apixaban, and edoxaban have emerged as an effective alternative to VKAs in the management of patients requiring anticoagulation. A recent systematic review of 10 studies reported that adverse events, including both major and minor bleeding events and failure of anticoagulation, as suggested by propagation of thrombus or recurrence of portal vein thrombosis, were similar between DOACs and VKAs for the treatment of acute portal vein thrombosis, irrespective of the presence of cirrhosis . Dabigatran, an important DOAC, is a direct thrombin inhibitor, and it does not rely on the presence of antithrombin for its action.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of 10 studies reported that adverse events, including both major and minor bleeding events and failure of anticoagulation, as suggested by propagation of thrombus or recurrence of portal vein thrombosis, were similar between DOACs and VKAs for the treatment of acute portal vein thrombosis, irrespective of the presence of cirrhosis. 8 Dabigatran, an important DOAC, is a direct thrombin inhibitor, and it does not rely on the presence of antithrombin for its action. Its clearance is via renal excretion in 80% individuals, and its pharmacokinetic profiles remain unaltered in patients with Child A and B cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Rivaroxaban has been increasingly used as an alternative to warfarin for the prevention of thrombosis in patients with venous thromboembolism (VTE) and atrial fibrillation [10] . It has been widely used in the treatment of deep venous thrombosis and pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%
“…The preventive dose is 10 mg once a day, and the therapeutic dose is 15 mg twice a day to 20 mg twice a day. Rivaroxaban can also be used in the treatment of portal vein thrombosis (PVT) in patients with and without cirrhosis [10,11] . However, in the current research and guidelines, the anticoagulant treatment of venous thromboembolism of atypical location (VTE-AL), such as the spleen, kidney, mesentery and portal vein, is still dominated by low molecular weight heparin and warfarin.…”
Section: Introductionmentioning
confidence: 99%